The future of Islamic finance : from Shari'ah Law to Fintech - Smolo, Edib; Raheem, Mohamed Mahees (Emerald Publishing Limited, 2024)
Islamic finance has witnessed a meteoric ascent in recent decades, cementing its status as a prominent player within the global financial sphere. Diverging from traditional financial systems, Islamic finance operates on the tenets of Shari'ah law, which emphasizes principles such as social equity, risk-sharing, and ethical investing. Although Islamic finance's appeal is evident within the Muslim community, its ethical and socially responsible investment options have begun to entice non-Muslims as well. Edited by Edib Smolo and Mohamed Mahees Raheem, this exhaustive collection presents an all-encompassing account of the current status of Islamic finance, accentuating its ethical, technological, and sustainable facets. The work is divided into four distinct parts which encompass the origin and evolution of Islamic finance, the underlying principles of Islamic finance and the primary disparities between Islamic finance and conventional financial systems, as well as the future of Islamic finance. Moreover, the collection explores the assimilation of Islamic finance principles into modern financial systems and the influence of Muslim scholars on present-day economic theories. The work emphasizes the significant contribution of Islamic finance in promoting sustainable development and social prosperity and underscores the incorporation of Islamic finance into the Sustainable Development Goals (SDGs). The work delves into the prospects and obstacles associated with the amalgamation of fintech and digital currencies into the Islamic finance sector and highlights the potential of green and sustainable finance in the digital era. This edited collection is designed for a wide range of professionals encompassing practitioners, policymakers, researchers, and students who are intrigued by the mounting significance of Islamic finance and its potential for the global financial sphere.
Keywords: Finance -- Religious aspects -- Islam.; Fintech.; Business & Economics -- Islamic Banking & Finance.; Shariah law: economics and finance.; Finance and the finance industry.; Relating to Islamic, Muslim people and groups.; elektronické knihy; electronic books